Tourism Sector's Contribution To Absorbing Labor In Indonesia - Syahiddin, Muhamad; Sumaryoto, Sumaryoto; Yolanda, Yolanda (PT Maju Malaqbi Makkarana, 2025)
The tourism sector plays a significant role in the Indonesian economy, both in terms of added value, foreign exchange earnings, and as a job creator. The panel data linear regression method is used to determine the effect of the tourism sector on labor absorption using panel data for 10 years of time series data and 41 cross-sectional data from districts/cities in three provinces in Indonesia. This quantitative research method using secondary data shows that cultural, ethnic, and linguistic diversity is a great potential in tourism development, while the creative economy sector has the potential to be a locomotive for increasing labor absorption. However, on the other hand, tourism is also one of the sectors most vulnerable to the COVID-19 pandemic.